Oviposition Strategies of Tachinid Parasitoids: Two Exorista Species as Case Studies. (20th February 2018) - Dindo, Maria Luisa; Nakamura, Satoshi
Oviposition strategies and mechanisms of host selection in parasitoids may be crucial for the success of parasitization and parasitoid production. These aspects are far less known in tachinid parasitoids than in hymenopteran parasitoids. Depending on the species, parasitoid flies may adopt direct or indirect oviposition strategies. The 'direct type' females lay eggs on or, in relatively a few species, inside the host body. This review describes cues involved in host selection by tachinid parasitoids and their oviposition strategies and presents 2 case studies in more detail, focusing on Exorista larvarum and Exorista japonica . These 2 polyphagous parasitoids of Lepidoptera lay macrotype eggs directly on the host cuticle. Both species have been used as biological control agents in inoculative release against the gypsy moth Lymantria dispar in the Northern United States. Improved knowledge of the mechanisms involved in host selection and oviposition strategies may increase the possibility of eliciting oviposition by these tachinids on target lepidopterous hosts (and even artificial substrates), thus facilitating their rearing and ultimately making their exploitation as regulators of target insect pests more feasible and efficient.